Squares of Hamiltonian cycles in 3‐uniform hypergraphs. Issue 2 (18th July 2019) - Bedenknecht, Wiebke; Reiher, Christian
Abstract : We show that every 3‐uniform hypergraph H  = ( V, E ) with | V ( H )| =  n and minimum pair degree at least (4/5 +  o (1)) n contains a squared Hamiltonian cycle. This may be regarded as a first step towards a hypergraph version of the Pósa‐Seymour conjecture.